Être étranger dans 'La Nouvelle Héloïse' - Nathalie Ferrand (Modern Languages Open)
‘He told me about his travels and, knowing he was English, I thought he was going to talk to me about buildings and paintings’ (La Nouvelle Héloïse, vol. 1, letter 45). In the preface to La Nouvelle Héloïse, Rousseau warns his readers to arm themselves with patience when confronted with the unfamiliar style of this collection of letters: ‘their writers are not French, wits, academicians, philosophers; but provincials, foreigners.’ In this fictional correspondence, individuals of different nationalities wield a quill, but not one of them is French. Instead we meet Swiss people, an English gentleman, a Russian prince of enigmatic origins, even an Italian prostitute. Yet there are many ways to be foreign in La Nouvelle Héloïse, and this issue extends far beyond that of mere nationalities. This great novel is populated by a multitude of foreign figures who correspond closely to those encountered by the historian Simona Cerutti in the course of her research for her book Étrangers: étude d’une condition d’incertitude dans une société d’Ancien Régime. This essay examines how this theme allowed Rousseau to interrogate the uncertainties of his own sense of belonging. Résumé ‘Il m’entretint de ses voyages, et le sachant Anglois, je crus qu’il m’alloit parler d’édifices et de peintures…’ (La Nouvelle Héloïse, t. 1, lettre 45). Dans la préface de La Nouvelle Héloïse, Rousseau avertit son lecteur. Celui-ci devra s’armer de patience face au style dépaysant de ce recueil de lettres: ‘ceux qui les écrivent ne sont pas des Français, des beaux-esprits, des académiciens, des philosophes; mais des provinciaux, des étrangers.’ Cette correspondance fictive met une plume dans la main de plusieurs personnages de différentes nationalités, mais pas d’un seul Français: des Suisses, un gentilhomme anglais, un prince russe à l’origine énigmatique, jusqu’à une prostituée italienne. Mais il est bien des manières d’être étranger dans La Nouvelle Héloïse, et cette question dépasse celle des nationalités. Une pluralité de figures de l’étranger peuplent ce grand roman qui correspondent remarquablement à celles qu’a rencontrées l’historienne Simona Cerutti au fil de l’enquête qu’elle a conduite dans Étrangers: étude d’une condition d’incertitude dans une société d’Ancien Régime. On se demandera comment un tel leitmotiv a pu permettre à Rousseau d’interroger les incertitudes de sa propre appartenance.